2016
DOI: 10.1186/s12879-016-1961-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome of Clostridium difficile infections in patients hospitalized in Internal Medicine: findings from the nationwide FADOI-PRACTICE study

Abstract: Background Clostridium difficile (CD) is a leading cause of diarrhoea among hospitalized patients. The objective of this study was to evaluate the rate, the optimal diagnostic work-up, and outcome of CD infections (CDI) in Internal Medicine (IM) wards in Italy.MethodsPRACTICE is an observational prospective study, involving 40 IM Units and evaluating all consecutive patients hospitalized during a 4-month period. CDI were defined in case of diarrhoea when both enzyme immunoassay for GDH, and test for A/B toxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
(48 reference statements)
0
7
0
5
Order By: Relevance
“…Se infatti consideriamo i risultati di un recente studio epidemiologico condotto in 40 centri italiani, notiamo come la percentuale di pazienti con CDI con almeno cinque comorbilità sia quasi doppia rispetto a quella riscontrata nella presente analisi (35,6% vs 18,9%) (14).…”
Section: Discussioneunclassified
See 3 more Smart Citations
“…Se infatti consideriamo i risultati di un recente studio epidemiologico condotto in 40 centri italiani, notiamo come la percentuale di pazienti con CDI con almeno cinque comorbilità sia quasi doppia rispetto a quella riscontrata nella presente analisi (35,6% vs 18,9%) (14).…”
Section: Discussioneunclassified
“…Se confrontata rispetto a quella determinata dagli studi condotti da Asensio et al (11) (12,5%) e da Cioni et al (14) (14,6%), la percentuale di soggetti con recidiva trovata in questa sede risulta sensibilmente inferiore (2,7%). Tuttavia tale differenza dipende dalle definizioni di recidiva adottate.…”
Section: Discussioneunclassified
See 2 more Smart Citations
“…1 Many studies in the last decade have reported an increasing number of C. difficile infections (CDIs). 2,3 The reported case fatality rates of CDIs are 6% to 30% and have been rising recently. 4,5 The infection increases not only patient mortality but also health care expenditures and length of hospital stay.…”
mentioning
confidence: 99%